Factors Influencing Employees’ Turnover Intention in the Indonesian Workforce: A Narrative Literature Review - Ida Ayu Widya Sariani; Komang Rahayu Indrawati (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Turnover intention is widely recognized as one of the earliest indicators of potential employee resignation, which in turn can generate considerable organizational challenges such as increased operational costs, the erosion of organizational knowledge, and declining productivity levels. While a significant body of international research has explored the antecedents of turnover intention, studies that specifically provide a narrative synthesis within the Indonesian workforce context remain scarce. Recognizing this gap, the present study seeks to identify the dominant factors that influence turnover intention in Indonesia by conducting a narrative literature review. The review focused on nine selected articles published between 2018 and 2023 in nationally indexed journals. To ensure rigor, the selection was based on predefined criteria: the articles had to employ empirical designs involving full-time employees, apply quantitative research methodologies, and explicitly examine the relationships between independent variables and turnover intention. The data extracted from the studies were analyzed thematically to identify recurring patterns and dominant themes. The analysis revealed four key factors that consistently shaped turnover intention across the reviewed literature. First, job stress was found to be a critical determinant, where prolonged work pressure and role overload significantly increased employees’ desire to leave. Second, job satisfaction emerged as a central variable, with dissatisfaction related to compensation, recognition, and career development strongly linked to turnover intention. Third, leadership style played an important role, as authoritarian or unsupportive leadership approaches heightened employees’ intention to resign. Finally, the leader’s role in fostering workplace relationships and support systems was identified as a factor influencing employee attachment and loyalty. In conclusion, this study contributes theoretically by mapping the dominant factors of turnover intention within the Indonesian context and highlights their interconnections.